The direct shear strength and dilatancy of sand-gravel mixtures - Simoni, A; Houlsby, G (2006)
A total of 87 direct shear tests in a large direct shear-box apparatus have been used to investigate the strength and dilatancy of sand-gravel mixtures. This paper focuses on the differences in behaviour between a silica sand (yellow Leighton Buzzard sand) and sand-gravel mixtures obtained by adding fractions of two kinds of gravel to the sand. The purpose is to find a relation between the grain-size characteristics of the materials and the shearing resistance. Experimental results are analysed in terms of the frictional and dilatant contributions to the strength of mixtures as a function of their relative density, and are compared with dilatancy theories and empirical equations. The addition of gravel to the mixtures, even at low fractions (less than 0.1 by volume), causes an increase in peak friction angle (φ′peak) which results both from higher dilatancy at failure (ψmax) and higher constant volume friction angle (φ′cv). Use of the minimum voids ratio (emin) of the materials allows the data for the two families of mixtures to be normalized and interpreted in terms of φ ′cv and the ratio (φ′peak -φ′cv/ψmax. The relationships between relative density (Dr), ψmax and φ′peak-φ′cv are only partly explained on a physical basis, so we develop empirical equations to predict the peak shear resistance of sand-gravel mixtures (up to gravel contents of 0.5) on the basis of easily measurable quantities. Such equations constitute a practical tool to overcome the problems arising from the impracticality of testing coarse material in the standard shear-box apparatus. © Springer 2006.